'Momentum rejuvenation' underlies the phenomenon of noise-assisted quantum energy flow. (27th January 2015) - Li, Ying; Caruso, Filippo; Gauger, Erik; Benjamin, Simon C
Abstract: An important challenge in quantum science is to fully understand the efficiency of energy flow in networks. Here we present a simple and intuitive explanation for the intriguing observation that optimally efficient networks are not purely quantum, but are assisted by some interaction with a 'noisy' classical environment. By considering the system's dynamics in both the site-basis and the momentum-basis, we show that the effect of classical noise is to sustain a broad momentum distribution, countering the depletion of high mobility terms which occurs as energy exits from the network. This picture suggests that the optimal level of classical noise is reciprocally related to the linear dimension of the lattice; our numerical simulations verify this prediction to high accuracy for regular 1D and 2D networks over a range of sizes up to thousands of sites. This insight leads to the discovery that dramatic further improvements in performance occur when a driving field targets noise at the low mobility components. The simulation code which we wrote for this study has been made openly available at figshare 4 .